A review of measuring ecosystem resilience to disturbance. (14th May 2021) - Yi, Chuixiang; Jackson, Nathan
Abstract: Resilience is the central concept for understanding how an ecosystem responds to a strong perturbation, and is related to other concepts used to analyze system properties in the face of change such as resistance, recovery, sustainability, vulnerability, stability, adaptive capacity, regime shift, and tipping point. It is extremely challenging to formulate resilience thinking into practice. The current state-of-art approaches of assessing ecosystem resilience may be useful for policy makers and ecosystem resource managers to minimize climatological or natural disaster related impacts. Here, we review the methods of assessing resilience and classify and limit them to three cases: (a) forest resilience based mainly on remote sensing and tree-ring data; (b) soil microbial community resilience based on laboratory and field studies; and (c) hydrological resilience of terrestrial biomes based on the Budyko framework and climate data.